PENGEMBANGAN BUKU CERITA ANAK BERGAMBAR BERBASIS NILAI-NILAI KEPEDULIAN BAGI PESERTA DIDIK KELAS 2 SEKOLAH DASAR - Vindaswari, Rera Fenika; Ulfah, Amaliyah (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
This study aims to develop pictorial children's storybooks based on caring values and specifically aims to know, (1) steps for developing child-based pictorial children's storybooks, (2) the feasibility of caring-based children's storybooks, and (3) participant responses students of story books developed.This type of research is development research. This study uses the Borg and Gall development model which consists of five stages, namely research and information collecting, planning, developing preliminary form a product, preliminary field testing, and main product revision. The subjects of this research were 10 second grade students of Banguntapan State Elementary School with 10 childrens. Data Collecting techniques use descriptive. The data analysis technique used is descriptive.The development of pictorial children's storybooks consists of six steps, namely determining themes, making storylines/storyboards, determining characters/figures, making illustrated images, combining storybook elements, and expert validation. The results of the study showed that illustrated children's storybooks were based on values of concern for second grade students of elementary school worthy of use. Assessment according to media experts got a score of 104 (good), material expert 101 (good), and expert learning 56 (very good). The response results of students get a score of 100 (very good). Students respond that the contents of illustrated story books are interesting, stories are easy to understand, and can be used as models in attitude.Keywords: Picture Children's Story Book, Concern Values